The Analysis of Agoraphobia and Defense Mechanism of Anna in Joe Wright’s Woman in the Window Movie - Tati Mardewi; Nurmala Dewi; Furi Indriyani; Masyifa Qurrota Aini (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2024)
This study analyzes the agoraphobia and defense mechanisms of Anna Fox in Joe Wright's The Woman in the Window. The research aims to determine the symptoms and defense strategies Anna utilizes to cope with her agoraphobia. A qualitative method with a descriptive focus was employed, involving in-depth movie observations and relevant document analysis. The analytic process begins by identifying Anna's agoraphobia symptoms and defense mechanisms, which are then examined in light of pertinent psychological theories. The results show that Anna exhibits three types of agoraphobia symptoms: physical, behavioral, and cognitive, in accordance with the National Health Service (NHS). 2022. Agoraphobia. England. The causes of Anna's agoraphobia are primarily psychological factors. Furthermore, Anna employs five defense mechanisms isolation, projection, rationalization, denial, and displacement to manage her anxiety. This study provides a comprehensive understanding of how individuals with anxiety disorders cope with their condition, offering valuable insights into the real-life application of these psychological concepts